Undernourished Children and Milk Lactose. (March 2016) - Grenov, Benedikte; Briend, André; Sangild, Per T.; Thymann, Thomas; Rytter, Maren H.; Hother, Anne-Louise; Mølgaard, Christian; Michaelsen, Kim F.
Background: Lactose is an important energy source in young mammals, and in fully breast-fed human infants, it constitutes around 40% of the total daily energy intake. The role of lactose in feeding of undernourished infants and young children is not well described. Objective: A narrative review of the potential positive and negative effects of lactose in the treatment of undernourished children. Methods: Searches were conducted using PUBMED and Web of Science up to July 2015. Relevant references in the retrieved articles were included. Results: Lactose may exhibit several health benefits in young children, including a prebiotic effect on the gut microbiota and a positive effect on mineral absorption. Studies in piglets suggest there might also be a stimulating effect on growth, relative to other carbohydrates. Lactose intolerance is a potential concern for undernourished children. Most undernourished children seem to tolerate the currently recommended (low lactose level) therapeutic foods well. However, a subgroup of severely undernourished children with secondary lactase deficiency due to severe diarrhea or severe enteropathy may benefit from products with even more restricted lactose content. At limited extra costs, lactose or lactose-containing milk ingredients may have beneficial effects if added to food products for undernourished children. Conclusions: Lactose may be an overlooked beneficial nutrient for young and undernourished children. Research is needed to define the balance between beneficial and detrimental effects of lactose in undernourished children at different ages and with different degrees of diarrhea and intestinal integrity.